A study on the measurement and determinants of profitability performance in Malaysian islamic banking institution / Siti Nurulhuda Ibrahim, Sharifah Heryati Syed Nor and Fahmi Abdul Rahim - Ibrahim, Siti Nurulhuda; Syed Nor, Sharifah Heryati; Abdul Rahim, Fahmi (Research Management Institute (RMI), 2010)
This study is able to measure the profitability performance of Malaysian Islamic Banking institution, whereby in the same time identify the determinants of its profitability from year to year that cover ten years period starting in year 2000 until 2009. Besides measure its performance from year to year, this study attempt to compare its profitability performance with conventional banking institution whether going parallel or not as targeted by BNM. Data has been analyzed by using ratio analysis when its become to measure its profitability performance. However, to identify the determinants of its profitability, the Least Square Method has been used.All data obtained straightly from secondary sources through published journal, books, working papers and etc.This study found that in terms of its profitabilty performance, the Islamic Banking Institution is moving parallel with Conventional banking institution. Meanwhile the most indicator that determine profitability of Malaysian Islamic Banking Institution is loan, whereby they have positive relationship that indicated increase(decrease) in loans would make increase (decrease) in profitability.However there is insignificant relationship for inflation and GDP growth rate with profitability of the Islamic Banking Institution.The finding also revealed that capital, cost of management and fuel price have significant relationship with profitability of this institution. As a conclusion, it is hoped that this study can give better understanding of Islamic Banking institution since now the islamic banking system play a vital role in the current global economic crisis.